A Stage of Emancipation Change and Progress at the Dublin Gate Theatre - Corporaal, Marguerite; van den Beuken, Ruud (Liverpool University Press, 2021)
As the prominence of the recent #WakingTheFeminists movement illustrates, the Irish theatre world is highly conscious of the ways in which theatre can foster social emancipation. This volume of essays uncovers a wide range of marginalised histories by reflecting on the emancipatory role that the Dublin Gate Theatre (est. 1928) has played in Irish culture and society, both historically and in more recent times. The Gate's founders, Hilton Edwards and Michéal mac Liammóir, promoted the work of many female playwrights and created an explicitly cosmopolitan stage on which repressive ideas about gender, sexuality, class and language were questioned. During Selina Cartmell's current tenure as director, cultural diversity and social emancipation have also featured prominently on the Gate's agenda, with various productions exploring issues of ethnicity in contemporary Ireland. The Gate thus offers a unique model for studying the ways in which cosmopolitan theatres, as cultural institutions, give expression to and engage with the complexities of identity and diversity in changing, globalised societies.